A call to arms : using theater to battle bullying among teens in Iceland - Jessica Marie Lo Monaco 1987- (2020)
Bullying, a worldwide problem that is complex and layered, can be especially challenging to teens and young adults. This paper is an in depth qualitative exploration of how theater programs that utilize Theater of the Oppressed methods and adapted versions of Forum Theater can be used to target bullying and increase conflict resolution among teens. This research explores in depth how improvisational theater paired with education on bullying can be used to address problems within society and how that may be used outside of a school setting in a small population like Iceland. Utilizing case studies, specifically the programs Acting Against Bullying and The Possibility Project that are directly and indirectly targeted at bullying, we can see the power of creating a language and culture that works towards communal prevention, intervention and peer education. This approach allows a unique and safe space for young people to explore ideas and try on the perspectives of their peers to work towards a lasting and motivated change. Exploring methods developed by Augusto Boal, we can see how these methods have been adapted and utilized in various contexts. Teens and young people are able to learn leadership and lead change in their communities, meaning this does not fall exclusively on the shoulders of teachers and schools, but rather community members in their free time, allowing intergenerational change to take place. The proposals for change in the conclusion include: teaching empathy and emotional communication in an environment that is safe for everyone, conflict resolution in a group or team setting and finally a cultural shift that challenges and changes the ideas of differences needing to be eradicated. In Iceland, which is rife with issues of bullying especially among young people, these techniques can create massive change for participants and all those around them. By incorporating initiatives like this into leisure centers and other venues outside of the school building, we can extend education and prevention ...